Searching for the Normal Vision. Measuring Visual Acuity in the 19th Century - Doria, Corinne (Medicina Historica, 2021)
This article aims to reconstruct and analyse the late-19th century debates about the standards used for measuring eyesight. It deals in particular with the creation of eye charts, one of the main tools used to assess visual acuity. My argument is organized as follow: I start by providing an account of the historical background against which modern eye charts were developed; the best-known of them will be discussed together with their characteristics. Next, I analyse the debates among ophthalmologists of the time about the definition of “normal eye” and “normal vision”, and show the divergence between the ones theoretically formulated and the data collected during clinical researches. Finally, I consider the question of sight measurement, looking on the one hand at the specialists’ desire to standardize a framework for measuring visual acuity, and on the other at the many obstacles in the way of achieving that aim.